A systematic review of outcomes reported in pediatric perioperative research: A report from the Pediatric Perioperative Outcomes Group. Issue 11 (27th October 2020) - Muhly, Wallis T.; Taylor, Elsa; Razavi, Cyrus; Walker, Suellen M.; Yang, Lei; de Graaff, Jurgen C.; Vutskits, Laszlo; Davidson, Andrew; Zuo, Yunxia; Pérez‐Pradilla, Carolina; Echeverry, Piedad; Torborg, Alexandra M.; et al.
Abstract: The Pediatric Perioperative Outcomes Group (PPOG) is an international collaborative of clinical investigators and clinicians within the subspecialty of pediatric anesthesiology and perioperative care which aims to use COMET (Core Outcomes Measures in Effectiveness Trials) methodology to develop core outcome sets for infants, children, and young people that are tailored to the priorities of the pediatric surgical population. Focusing on four age‐dependent patient subpopulations determined a priori for core outcome set development: (a) neonates and former preterm infants (up to 60 weeks postmenstrual age); (b) infants (>60 weeks postmenstrual age—<1 year); (c) toddlers and school age children (>1‐<13 years); and (d) adolescents (>13‐<18 years), we conducted a systematic review of outcomes reported in perioperative studies that include participants within age‐dependent pediatric subpopulations. Our review of pediatric perioperative controlled trials published from 2008 to 2018 identified 724 articles reporting 3192 outcome measures. The proportion of published trials and the most frequently reported outcomes varied across predetermined age‐groups. Outcomes related to patient comfort, particularly pain and analgesic requirement, were the most frequent domain for infants, children, and adolescents. Clinical indicators, particularly cardiorespiratory or medication‐related adverse events, were the most common outcomes for neonates and infants <60 weeks and were the second most frequent domain at all other ages. Neonates and infants <60 weeks of age were significantly under‐represented in perioperative trials. Patient‐centered outcomes, healthcare utilization, and bleeding/transfusion‐related outcomes were less often reported. In most studies, outcomes were measured in the immediate perioperative period, with the duration often restricted to the postanesthesia care unit or the first 24 postoperative hours. The outcomes identified with this systematic review will be combined with patient‐centered outcomes identified through a subsequent stakeholder engagement study to arrive at a core outcome set for each age‐specific group.